Effect of surface roughness and chemistry on the adhesion and durability of a steel-epoxy adhesive interface. (January 2020) - van Dam, J.P.B.; Abrahami, S.T.; Yilmaz, A.; Gonzalez-Garcia, Y.; Terryn, H.; Mol, J.M.C.
Abstract: This work focuses on the effect of surface roughness and surface chemistry on the initial adhesion strength and corrosive de-adhesion properties of adhesive bonds. The adherend used in this study is a S690 low-alloy steel whereas the adhesive is a 2-component epoxy-amine adhesive (Araldite 2015). The steel surface is subjected to different surface pre-treatment methods such as mechanical abrasion, grit blasting, zirconium conversion treatment and silane treatment. The effect of these different pre-treatments on the surface morphology, roughness and chemistry is addressed. Single-lap joint tests were performed at ambient conditions to assess the initial bond strength of the joint. Static wedge tests were performed in saltwater immersions to study the environmental ageing of the adhesive joints. Unloaded delamination of adhesive films from the steel surface was studied by means of scanning Kelvin probe (SKP) at high relative humidity. This unique combination of different techniques allows thorough evaluations of the bond performance under different environmental and loading conditions. Experimental results indicate that surface roughening plays an important role in the initial adhesion in the single-lap joint test but a minor role in the durability of the bonded steel surfaces. The improved initial adhesion is mainly attributed to the increased interfacial bond area at higher surface roughness. The presence of complex texture or morphology shows a more profound effect than the average roughness on both the initial adhesion and the durability of the interfacial adhesion. The results from the static wedge test show the large contribution of mechanical interlocking, caused by texturing of the surface, on the durability of the interfacial adhesion. In the absence of complex texture, surfaces with altered chemistry by zirconium- or silane treatment exhibit a significant increase of the initial bonding strength due to enhanced physicochemical interactions across the interface. Assessment of the interfacial delamination kinetics by SKP show that despite the absence of any surface topography, chemically altered surfaces prove to have higher resistance to delamination. Graphical abstract: Image 1